The early childhood coaching handbook - Rush, Dathan D.; Shelden, M'Lisa L. (Paul H. Brookes Publishing Co., 2020)
"... this book walks you step-by-step through the five characteristics of successful coaching practices: observation, action, reflection, feedback, and joint planning. You'll learn about the essential qualities of effective coaches and discover how to adjust your coaching techniques to meet the specific needs of early childhood educators, parents, and caregivers. ... Practical forms now available as fillable PDFs for download ..."- Resumé vydavatel
Keywords: vývoj dítěte; předškolní výchova; koučování; učitelé mateřských škol; speciální pedagogika; child development; preschool education; personal coaching; preschool teachers; special education; elektronické knihy; příručky; electronic books; handbooks and manuals